If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8v+13=7v-11
We move all terms to the left:
8v+13-(7v-11)=0
We get rid of parentheses
8v-7v+11+13=0
We add all the numbers together, and all the variables
v+24=0
We move all terms containing v to the left, all other terms to the right
v=-24
| 33+6x=3(-1 | | 4r-5+3(2r-8)=111 | | -18+2=-2(x+3) | | -(v-70)=63 | | 211/12x3/4=x | | 450=(40*x)+(1.5*x) | | 456=-8(-8x-9) | | 42=-3x=54 | | 5x+14=x-1 | | 9+19=-4(7x-7) | | 190=10(-5x-6) | | -10(w-89)=-80 | | 190=10(-5x-6 | | y+6=18/2 | | 5(4x+9)=-24+49 | | -5+4u=-29 | | 3x-(7x+20)=6-(13x-3) | | 52-2(y-4)-yy=14 | | 2(4x+9)=-21+7 | | m+19/7=4 | | (w+3)-2w-(1-3w)=2 | | 4(v-3)-5=-3(-8v+9)-4v | | 2(w+7)-4w=20 | | -304=194+-3q | | -9=-11+(b)/(8) | | 3x+7=5x-11=52-2x | | -9c-18=-81 | | 12x-28=24 | | 5(2x+6)=-43+3 | | x4-56=98 | | 4(v-3)-5=-3(-8+9)-4v | | -34=4v+6(v-4) |